Rancang Bangun Aplikasi Persediaan Bahan Baku Pada CV Lintas Nusa SUrabaya - Indarwati, Iin; Tjandrarini, A B; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV Lintas Nusa Surabaya is an offset printing that produces brochures, labels, hang tags, etc. The company carries out production according by customer orders (make to order). So far, the company often experience shortages of raw materials when production, so it resulting in time delays when it meets the customer orders. This is due to lack of control on inventory in the warehouse and not careful to prepare the raw material requirement before the production process.Based on these problems, the company need an application to forecast the raw material inventory  using Single Exponential Smoothing method. In that system, there are several process, is selecting previous periods of customer demand, selecting the finished goods, calculating the raw material requirement by demands, and forecasting the raw material requirement for three periods ahead.That application produce the forecasting results report and raw material requirements report. Based on the applications made and some of trials that have been done, the company be able to know the information needed, especially about the meet raw material requirements such as what raw materials should be prepared before the production process. Keywords : Forecasting, Raw Material Inventory, Single Exponential Smoothing